2016
DOI: 10.1038/mi.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Tissue heme oxygenase-1 exerts anti-inflammatory effects on LPS-induced pulmonary inflammation

Abstract: Heme oxygenase-1 (HO-1) has been shown to display anti-inflammatory properties in models of acute pulmonary inflammation. For the first time, we investigated the role of leukocytic HO-1 using a model of HO-1(flox/flox) mice lacking leukocytic HO-1 that were subjected to lipopolysaccharide (LPS)-induced acute pulmonary inflammation. Immunohistology and flow cytometry demonstrated that activation of HO-1 using hemin decreased migration of polymorphonuclear leukocytes (PMNs) to the lung interstitium and bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 64 publications
5
55
0
4
Order By: Relevance
“…This corroborates previous studies that showed a reduction in the breakdown of alveolar capillary barriers in models of ALI/ARDS induced by LPS [42]. Additionally, in experimental cerebral malaria, the induction of HO-1 reduced the permeability of the blood brain barrier in PbA infected mice [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This corroborates previous studies that showed a reduction in the breakdown of alveolar capillary barriers in models of ALI/ARDS induced by LPS [42]. Additionally, in experimental cerebral malaria, the induction of HO-1 reduced the permeability of the blood brain barrier in PbA infected mice [16].…”
Section: Discussionsupporting
confidence: 91%
“…Increased levels of MCP-1, chemokine involved in recruiting of monocytes, neutrophils, and lymphocytes, were found in pulmonary alveolar macrophages isolated from a rat model of immune complex-mediated acute inflammatory lung injury [41]. This shows that hemin reduced the levels of inflammatory cytokines that are important in ALI/ARDS, which corroborates with previous results showing that HO-1 induction by hemin has anti-inflammatory effects in models of sepsis and LPS induced ALI/ARDS in mice [25, 42]. As an anti-inflammatory cytokine, which was increased in hemin treated animals, which were protected against endotoxic shock [43] and whose effect in ALI/ARDS was shown to be protective [44], IL-10 was not expected to be decreased in hemin treated animals in our data.…”
Section: Discussionsupporting
confidence: 86%
“…They determined the main expression of the chemokine SDF-1 in the alveolar epithelium and alveolar macrophages during acute pulmonary inflammation. The predominant effect of CXCR7 on pulmonary epithelium is further supported by our findings from the chemokine assay with a significant reduction of CXCL1, which is mainly released by the pulmonary epithelium (11,14,15). The reduction of the PMN chemoattractant CXCL2/3, mainly secreted by alveolar macrophages (11), is also in line with the above-mentioned findings from Petty et al (7).…”
Section: Discussionsupporting
confidence: 80%
“…Thereby, CXCL1 is mainly released by the epithelium, and CXCL2/3 is released by alveolar macrophages and PMNs (11,14,15). LPS exposure induced the release of both chemokines after 3 and 24 h (all p , 0.05) (Fig.…”
Section: Cxcr7 Inhibition Ameliorated the Release Of Inflammatory Chementioning
confidence: 99%
See 1 more Smart Citation